Parametric analysis of the influence of vertical reinforcement of soil bases with rigid elements on increasing the deformation modulus and structural stability - SAMCHENKO, Roman; KONDRATUK, Ruslan (Ways to Improve Construction Efficiency, 2025)
This paper is dedicated to investigating the impact of vertical reinforcement of soil bases with rigid elements on enhancing the deformation modulus and overall structural stability. The primary objective is to establish optimal reinforcement parameters, including the selection of rigid element materials, to ensure increased bearing capacity and reduced base deformations. Furthermore, a comparative analysis of reinforcing elements made from various materials (reinforced concrete, steel, soil-cement, composite materials) is conducted, evaluating their advantages and disadvantages. The study employs analytical calculation methods, a comparative analysis of existing experimental results, an examination of regulatory documentation, and empirical models to assess the effectiveness of different reinforcement techniques (soil mixing piles, jet grouting, composite reinforcement, metallic elements). To obtain the results, a comparison of the influence of various reinforcement types on the increase in the soil deformation modulus was performed. It was found that soil mixing pile technology allows for an increase in the deformation modulus by up to 70%, while the application of jet grouting more than doubles it. It was established that composite materials exhibit low corrosion susceptibility but are inferior in terms of elastic modulus to steel reinforcing elements. Optimal application areas for different reinforcement technologies are proposed based on soil type and operational conditions. The scientific novelty of this research lies in the systematic analysis of the influence of vertical reinforcement with rigid elements on the change in the deformation modulus of soil bases, which allows for the development of optimal parametric recommendations for foundation design in various geotechnical conditions. The obtained results can be utilized in the design of foundation bases, contributing to a more effective solution to the problem of ensuring the stability of buildings and structures in complex engineering-geological conditions.